(untitled) (Marketing Journal, 2025)
This article provides a comprehensive analysis of the development processes of the garment industry in the Republic of Uzbekistan, focusing on its economic potential and market position. The implementation of innovative technologies and systematic moderniz ation efforts are examined to enhance industry competitiveness. The distinctive features of domestic and international markets, their demands and opportunities, are explored, accompanied by recommendations related to economic strategies. The study summariz es analytical results based on advanced market development methodologies, statistical data, and government policy.